Examination of the effects of globalization over physical education and sports academies (sample of Ankara) - İmran Akdagcık; Suat Karakucuk (Selcuk University, 2013)
One of the most discussed topics in recent years is the question of globalization or nationalization(regionalization). In other words, strong capital dominated policy and modernizing technology, religion, andnational identity, tradition, protection of cultural and linguistic differences on the resistance created. One of themajor areas affected by the globalization is education and training institutions. The purpose of this study is todetermine the viewpoints of academic staff related to the expected and observed effects of globalization on thedimensions of administration, finance, technology, research and instruction, and whether there are significantdifferences between academic staff' viewpoints of expected and observed effects of globalization. The items weregrouped in relating with the dimensions of administration, finance, technology, research and instruction. Thereliability and validity analysis was made and Cronbach alfa reliability coefficient was found 0.98. Means, pairedt- tests, non-paired t test, One way ANOVA and LSD were used in the analysis of data. According to the resultsof this research, academic staffs in PESA (Physical Education and Sports Academies) evaluate the effects ofglobalization as expected ones. However they assert that they could not entirely observe the expected effects ofthe referred dimensions of globalization.